1987
DOI: 10.1002/ajh.2830260210
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose chemoradiotherapy with syngeneic bone marrow transplantation for multiple myeloma: A case report and literature review

Abstract: We had the opportunity to treat a patient with progressive heavily pretreated multiple myeloma with high-dose chemoradiotherapy with hematopoietic rescue by syngeneic bone marrow transplantation. The patient was a 53-year-old male who had previously received melphalan, prednisone, 1,3-bis (2-chloroethyl)-l-nitrosourea (BCNU), vincristine, and standard radiation therapy. At the time of bone marrow transplantation, he had increasing bone pain, increasing M-protein (IgG kappa), and a bone marrow diagnostic of mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[4][5][6] The largest series reported includes 11 patients and in five of them complete remission (CR) was achieved after high-dose cyclophosphamide and TBI. In four of the five patients, having IgG kappa MM, the CR was maintained for years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] The largest series reported includes 11 patients and in five of them complete remission (CR) was achieved after high-dose cyclophosphamide and TBI. In four of the five patients, having IgG kappa MM, the CR was maintained for years.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of MM patients treated with syngeneic BMT have been reported in the literature and in some of them prolonged remissions have been observed. [4][5][6] In this report, we describe a MM patient with a localized and extramedullary relapse after a 7-year remission following syngeneic BMT. …”
mentioning
confidence: 99%
“…Two studies have reported the long‐term follow‐up of patients who received syngeneic bone marrow transplants for multiple myeloma. The first study in 1996 reported the Seattle experience in 11 patients with advanced myeloma (29–31). All patients received myeloablative therapy; (5 patients 45%) achieved CR and (3 patients 27%) had a PR.…”
Section: Comparison Of Allogeneic and Syngeneic Transplant For Myelomamentioning
confidence: 99%